1998
DOI: 10.1128/jb.180.1.52-58.1998
|View full text |Cite
|
Sign up to set email alerts
|

The Capsule and S-Layer: Two Independent and Yet Compatible Macromolecular Structures in Bacillus anthracis

Abstract: Bacillus anthracis, the etiological agent of anthrax, is a gram-positive spore-forming bacterium. Fully virulent bacilli are toxinogenic and capsulated. Two abundant surface proteins, including the major antigen, are components of the B. anthracissurface layer (S-layer). The B. anthracis paracrystalline S-layer has previously only been found in noncapsulated vegetative cells. Here we report that the S-layer proteins are also synthesized under conditions where the poly-γ-d-glutamic acid capsule is present. Stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(47 citation statements)
references
References 34 publications
2
44
0
Order By: Relevance
“…The Vi antigen is able to mask the O-antigen in S. typhi, indicating that the cell surface-associated polysaccharide constitutes a large capsule-like structure at the bacterial surface. Interestingly, it has also been demonstrated that the S-layer proteins are inaccessible to antibodies in capsulated strains of Bacillus anthracis (Mesnage et al, 1998). Hence, it is plausible that the Vi capsular polysaccharide might act as a physical barrier impairing the secretion of premade Sip proteins, even when the Inv-Spa-Prg secretion apparatus is active.…”
Section: Discussionmentioning
confidence: 99%
“…The Vi antigen is able to mask the O-antigen in S. typhi, indicating that the cell surface-associated polysaccharide constitutes a large capsule-like structure at the bacterial surface. Interestingly, it has also been demonstrated that the S-layer proteins are inaccessible to antibodies in capsulated strains of Bacillus anthracis (Mesnage et al, 1998). Hence, it is plausible that the Vi capsular polysaccharide might act as a physical barrier impairing the secretion of premade Sip proteins, even when the Inv-Spa-Prg secretion apparatus is active.…”
Section: Discussionmentioning
confidence: 99%
“…The only surface component that can be excluded as the attachment site is the S-layer that covers the bacterium and is located between the PG and the capsule. Indeed, S-layer and capsule are two compatible and yet independent structures (Mesnage et al ., 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, AtxA co-ordinates an important regulatory network, which might extend to chromosomal genes. Our laboratory has been studying the S-layer, a major protein network that covers the cell surface underneath the capsule (Mesnage et al ., 1998). Through studies of a plasmidless strain, we have shown previously that the composition of this structure is growth phase regulated, so that exponential phase cells are covered by the Sap protomers, whereas stationary phase cells are covered by the EA1 protomers (Mignot et al ., 2002).…”
Section: Introductionmentioning
confidence: 99%